2015
DOI: 10.1007/s10552-015-0678-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparing SurePath, ThinPrep, and conventional cytology as primary test method: SurePath is associated with increased CIN II+ detection rates

Abstract: PurposeWithin the last decade, SurePath and ThinPrep [both liquid-based cytology (LBC) tests] have replaced conventional cytology (CC) as primary test method in cervical cancer screening programs of multiple countries. The aim of our study was to examine the effect in the Dutch screening program.MethodsAll primary smears taken within this program from 2000 to 2011 were analyzed using the nationwide registry of histo- and cytopathology (PALGA) with a follow-up until March 2013. The percentage of smears classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 35 publications
3
43
1
5
Order By: Relevance
“…Fontaine et al have shown that unsatisfactory rates are significantly lower when using SurePath instead of ThinPrep. 44 Although this was not shown in our previous study, 19 we then found similar results (an odds ratio of 0.74, 0.72 to 0.75) when comparing unsatisfactory rates between SurePath and ThinPrep.…”
Section: Explanation Of Main Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Fontaine et al have shown that unsatisfactory rates are significantly lower when using SurePath instead of ThinPrep. 44 Although this was not shown in our previous study, 19 we then found similar results (an odds ratio of 0.74, 0.72 to 0.75) when comparing unsatisfactory rates between SurePath and ThinPrep.…”
Section: Explanation Of Main Resultssupporting
confidence: 69%
“…19 As the use of SurePath resulted in decreased rates of cervical cancer after a normal screening sample, this indicates that at least part of the extra detected CIN lesions were progressive. As the use of ThinPrep seemed to result in increased cancer rates, this suggests that fewer of the detected CIN lesions were progressive.…”
Section: Explanation Of Main Resultsmentioning
confidence: 99%
“…There are few studies comparing different methods of LBC. Published studies have shown better performance of SurePath® over Thinprep® in the detection of significant lesions [15, 16]. However, ours is the first study addressing the performance of a new and cheaper fixative, thereby making this method affordable and universal in the treatment of LBC for low-income countries.…”
Section: Discussionmentioning
confidence: 95%
“…Meta-analyses suggest that the diagnostic accuracy of cytology does not vary by collection method (i.e., conventional Pap smear versus liquid-based cytology), although liquid-based collection may result in fewer inadequate tests and is preferable because it allows reusing the sample for HPV testing (i.e., reflex testing) [35,37]. However, recent studies suggest that the sensitivity for detecting CIN2+ depends on the type of liquid-based cytology test [38,39]. In contrast to cytology, HPV DNA tests are automated and [40]), which detects presence or absence of HPV DNA.…”
Section: Principles and Aspects Of Cervical Cancer Screeningmentioning
confidence: 99%